Financial Deepening and Economic Growth in Indonesia - Putri, Syifa Annisa; Nadila, Nadila; Kirana, Yeremia Sahat; Suhendra, Indra; Anwar, Cep Jandi (JAMPARING: Jurnal Akuntansi Manajemen Pariwisata dan Pembelajaran Konseling, 2025)
The financial sector is critical to improving economic growth and cannot be separated from a country's economic growth. Consequently, financial deepening is an effort by the financial sector to reduce dependence on offshore savings. The purpose of this study is to evaluate the impact of financial deepening on Indonesia's economic growth by looking at various variables such as M2/GDP, Banking Credit, Inflation, Bank Indonesia Interest Rate, and Exchange Rate. The secondary data used in this study ranges from 2010 Q1 to 2022 Q4. This study uses the Vector Error Correction Model (VECM). The results showed that the variables M2/GDP, Banking Credit, and Bank Indonesia Interest Rate have a significant positive influence on Economic Growth. In contrast, Inflation and Exchange Rate variables have a significant positive effect on Economic Growth.